2015
DOI: 10.1542/neo.16-4-e236
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Fetal Exposure to Toxoplasmosis

Abstract: Symptomatic congenital toxoplasmosis is a rare disease in the United States. However, prenatal screening is becoming increasingly available, resulting in identification of infants at risk of developing the disease. Infants who are born asymptomatic may still develop significant neurodevelopmental sequelae months or even years after birth if untreated. Congenital toxoplasmosis is a difficult infection to diagnose. Using one case as an example, this review attempts to highlight the importance of identifying at-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Illness can range from non-specific systemic symptoms such as fever, lymphadenopathy and hepatosplenomegaly to congenital toxoplasmosis (CT), which is classically described as a triad of chorioretinitis, intracranial calcifications and hydrocephalus. CT can lead to loss of vision and hearing, decreased cognitive function, and neurodevelopmental delay if untreated [14,[16][17][18].…”
Section: Toxoplasmosismentioning
confidence: 99%
See 3 more Smart Citations
“…Illness can range from non-specific systemic symptoms such as fever, lymphadenopathy and hepatosplenomegaly to congenital toxoplasmosis (CT), which is classically described as a triad of chorioretinitis, intracranial calcifications and hydrocephalus. CT can lead to loss of vision and hearing, decreased cognitive function, and neurodevelopmental delay if untreated [14,[16][17][18].…”
Section: Toxoplasmosismentioning
confidence: 99%
“…gondii exists in three forms: tachyzoite, bradyzoite, and sporozoite. The definitive hosts are members of the Felidae family, but warm-blood mammals can also serve as intermediate hosts [17]. Felines can acquire T. gondii through the ingestion of tissue cysts containing bradyzoites in infected prey or through the ingestion of oocysts containing sporozoites in anything contaminated with feces from an infected cat.…”
Section: Toxoplasmosismentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, they may still develop significant neurodevelopmental sequelae and chorioretinitis months or even years after birth if are left untreated. 3 Studies have demonstrated that screening and treatment for toxoplasmosis during pregnancy can help to decrease the vertical transmission and the clinical sequelae thereafter. 4…”
Section: Introductionmentioning
confidence: 99%